Assessment of the reproducibility and inter-site transferability of the murine direct splenocyte mycobacterial growth inhibition assay (MGIA) - Tanner, R; Zelmer, A; Painter, H; Stylianou, E; Pinpathomrat, N; Harrington-Kandt, R; Biffar, L; Brennan, MJ; McShane, H; Fletcher, HA (Cold Spring Harbor Laboratory, 2021)
Tuberculosis (TB) vaccine candidates must be tested for safety and efficacy using preclinical challenge models prior to advancement to human trials, because of the lack of a validated immune correlate or biomarker of protection. New, unbiased tools are urgently needed to expedite the selection of vaccine candidates at an early stage of development and reduce the number of animals experimentally infected with virulent Mycobacterium tuberculosis (M.tb). In recent years, there has been a concerted effort to develop standardised functional ex vivo mycobacterial growth inhibition assays (MGIAs) as a potential surrogate read-out of vaccine efficacy. We have previously described a direct MGIA for use with mouse splenocytes. In the current study, we set out to systematically compare co-culture conditions for the murine direct splenocyte MGIA with respect to both intra-assay repeatability and inter-site reproducibility. Common sample sets were shared between laboratory sites and reproducibility and sensitivity to detect a BCG-vaccine induced response were assessed. Co-culturing 5×106 splenocytes in 48-well plates resulted in improved reproducibility and superior sensitivity to detect a vaccine response compared with standing or rotating sealed 2ml screw-cap tubes. As the difference between naïve and BCG vaccinated mice was not consistently detected across both sample sets at both sites, we sought to further improve assay sensitivity by altering the multiplicity of infection (MOI). Cell viability at the end of the co-culture period was improved when splenocyte input number was reduced, with the highest viability for the condition of 3×106 splenocytes in 48-well plates. This cell input was also associated with the greatest sensitivity to detect a BCG vaccine-mediated MGIA response using an M.tb inoculum. Based on our findings, we recommend optimal co-culture conditions in a move towards aligning direct MGIA protocols and generating a cross-species consensus for early evaluation of TB vaccine candidates and biomarker studies.